(untitled) (Ocean and Coastal Research, 2022)
Iron is a limiting nutrient for Symbiodiniaceae (colloquially known as zooxanthellae), with low solubility in seawater. The use of stable, soluble, and chemically defined iron complexes is proposed as a strategy to control the supply of this metal to target organisms. In this work, we investigated the effect of iron(II) and derivatives of iron(III) (desferrioxamine, deferiprone, deferasirox, and HBED) over the growth and metal loading of five Symbiodiniaceae species. Iron supplementation did not affect growth or metal load in species with high iron stocks. In contrast, for species with low iron stocks, hydrophobic Fe(DFX)2 was very efficient in inducing growth and iron loading. Also, the desferrioxamine derivative of iron Fe(DFO) appeared as an interesting, ecologically friendly source of the nutrient. The effect of iron supplementation on the growth of Breviolum minutum submitted to heat shock was also studied. Iron supplementation prior to the heat shock episode increased the heat tolerance of B. minutum. Such findings provide new insights for the strategy of iron supplementation to improve the fitness of Symbiodiniaceae, both in vitro and in the environment.